Delta Protocadherin 10 is Regulated by Activity in the Mouse Main Olfactory System - Williams, Eric O.; Sickles, Heather M.; Dooley, Alison L.; Palumbos, Sierra; Bisogni, Adam J.; Lin, David M. (Frontiers in Neural Circuits, 2011)
Olfactory sensory neurons (OSNs) are thought to use activity-dependent and independent mechanisms to regulate the expression of axon guidance genes. However, defining the molecular mechanisms that underlie activity-dependent OSN guidance has remained elusive. Only a handful of genes have been identified whose expression is regulated by activity. Interestingly, all of these genes have been shown to play a role in OSN axon guidance, underscoring the importance of identifying other genes regulated by activity. Furthermore, studies suggest that more than one downstream mechanism regulates target gene expression. Thus, both the number of genes regulated by activity and how many total mechanisms control this expression are not well understood. Here we identify delta protocadherin 10 (pcdh10) as a gene regulated by activity. Delta protocadherins are members of the cadherin superfamily, and pcdh10 is known to be important for axon guidance during development. We show pcdh10 is expressed in the nasal epithelium and olfactory bulb in patterns consistent with providing guidance information to OSNs. We use naris occlusion, genetic manipulations, and pharmacological assays to show pcdh10 can be regulated by activity, consistent with activation via the cyclic nucleotide-gated channel. Transgenic analysis confirms a potential role for pcdh10 in OSN axon guidance.